2018
DOI: 10.1128/mbio.00648-18
|View full text |Cite
|
Sign up to set email alerts
|

Cwp19 Is a Novel Lytic Transglycosylase Involved in Stationary-Phase Autolysis Resulting in Toxin Release in Clostridium difficile

Abstract: Clostridium difficile is the major etiologic agent of antibiotic-associated intestinal disease. Pathogenesis of C. difficile is mainly attributed to the production and secretion of toxins A and B. Unlike most clostridial toxins, toxins A and B have no signal peptide, and they are therefore secreted by unusual mechanisms involving the holin-like TcdE protein and/or autolysis. In this study, we characterized the cell surface protein Cwp19, a newly identified peptidoglycan-degrading enzyme containing a novel cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 92 publications
(115 reference statements)
5
61
0
Order By: Relevance
“…In that study, Wydau‐Dematteis et al . (Wydau‐Dematteis et al ., ) proved that TcdE and bacteriolysis were coexisting mechanisms for toxin release, with their relative contributions in vitro depending on growth conditions (works in BHIS not in TY). In this study, we also detected the increase of autolysis and cell permeability of the cwp22 mutant compared with the parent strain.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In that study, Wydau‐Dematteis et al . (Wydau‐Dematteis et al ., ) proved that TcdE and bacteriolysis were coexisting mechanisms for toxin release, with their relative contributions in vitro depending on growth conditions (works in BHIS not in TY). In this study, we also detected the increase of autolysis and cell permeability of the cwp22 mutant compared with the parent strain.…”
Section: Discussionmentioning
confidence: 94%
“…(Olling et al ., ) identified that the release of toxin from C. dificile 630Δ erm is not affected by the inactivation of the tcdE gene. Recently, it was identified that Cwp19 acts as a novel lytic tansglycosylase, which is involved in toxin release through stationary‐phase autolysis in C. difficile 630Δ erm (Wydau‐Dematteis et al ., ). In that study, Wydau‐Dematteis et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations